Pengaruh Pemadatan Dua-arah Penekanan terhadap Densitas dan Kekerasan AMC diperkuat Serbuk Silikon Dioksida - Ricky Irwansyah; Rodika Rodika; Agus Wanto; Mego Wahyudi; Sukanto Wiryono (Infotekmesin, 2023)
The compaction method of powder metallurgy technology is an important process in influencing the density and hardness of the resulting product. This study aims to determine the effect of a one-way compaction method compared to a two-way compaction method on the density and hardness of the resulting composite product. The experimental method for making aluminum matrix composites with silica sand reinforcement applies a compaction pressure of 4500 Psi. Mixing utilizing mechanical alloying used a horizontal ball mill machine. The density test refers to the Archimedes principle with the ASTM B962-17 standard, while the Rockwell Brinel hardness test uses the ASTM E110-14 standard. The results of the sample density test of the two-way compaction method of compaction showed a higher value compared to the sample density of the one-way compaction results, respectively; values of 2.132 g/cm3 and 2.119 g/cm3. The hardness value of the sample resulting from two-way compression compaction also has a higher value than the sample hardness resulting from one-way compression compaction, respectively; worth 43.67 HRB and 36.78 HRB. Furthermore, based on the results of microstructural analysis, the interlocking bonding occurs in composite samples with two-way compaction. It is also better than the interlocking mechanical bonding in composite samples resulting from one-way compaction.